2021
DOI: 10.3390/jrfm14120579
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Determinants of Capital Structure in the Greek Pharmaceutical, Cosmetic and Detergent Industries

Abstract: The purpose of this paper is to investigate the relationship between a firm’s capital structure (i.e., leverage) and its operating environment, taking into account firm (i.e., efficiency, asset structure, profitability, size, age and risk) and industry effects. For a sample of Greek pharmaceutical, cosmetic and detergent (PCD) enterprises, firm efficiency was estimated using bootstrapped data envelopment analysis (DEA), and a leverage model was produced using ordinary least squares (OLS) regression. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the cosmetics industry, larger firms benefit from economies of scale in terms of reduced unit costs because of their higher production volumes. According to Tsolas (2001) companies with larger revenues can achieve economies of scale from greater bargaining power to negotiate lower production costs, marketing expenses, and distribution costs. Similarly, companies with larger assets have better access to finances, which can help them capitalize on various opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the cosmetics industry, larger firms benefit from economies of scale in terms of reduced unit costs because of their higher production volumes. According to Tsolas (2001) companies with larger revenues can achieve economies of scale from greater bargaining power to negotiate lower production costs, marketing expenses, and distribution costs. Similarly, companies with larger assets have better access to finances, which can help them capitalize on various opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, a proactive approach to identifying and addressing inefficiencies is essential for preserving and enhancing future profitability. This might involve process optimization, restructuring, or a reassessment of resource allocation strategies (Tsolas, 2021). By leveraging financial metrics and conducting a comprehensive analysis, stakeholders can gauge the effectiveness of a firm's cost management practices and its resilience in the face of evolving market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the analysis of the capital structure-firm performance relationship in CEE countries was extended for another nine-year period, that is, from 2008 to 2017. Furthermore, only a few studies investigating the association between capital structure and firm performance have focused on the reverse causality from performance to capital structure (Berger and Bonaccorsi di Patti, 2006;Margaritis and Psilallaki, 2007;Tsolas, 2021). To analyze this reverse causality, two opposite hypotheses have been proposed (Berger and Bonaccorsi di Patti, 2006), namely the efficiency-risk hypothesis and the franchise-value hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The few empirical studies that investigated the reverse causality from performance to capital structure have revealed mixed results (Berger and Bonaccorsi di Patti, 2006;Margaritis and Psilallaki, 2007;Tsolas, 2021). For example, Berger and Bonaccorsi di Patti (2006) found support for the efficiency-risk hypothesis for US banking industry, whereas Tsolas (2021) found support for the franchise-value hypothesis for the Greek firms. Margaritis and Psilallaki (2007) showed that both hypotheses might explain the relationship between firm performance and capital structure.…”
Section: Introductionmentioning
confidence: 99%